STRATEGI PENGEMBANGAN RURAL TOURISM DI WILAYAH JAZIRAH LIEHITU: STUDY KASUS DESA TULEHU DAN DESA LIANG KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Maimunah Toatubun (TAHKIM, 2018)
The aim of research are to: (1) To identified and find out potensial and “capital” to developed stategy for Rural tourism in both Village (Tulehu and Liang), (2) To estimate Readiness Governance of Rural to develop strategy Rural Tourism, (3) to find out the support and participation of local communities to develop strategy rural tourism, (4) To know perception local, national tourism and the relationship to develop rural tourism. The result showed that: (1) Tulehu village had more potencial in rural tourism than Liang village, (2) The local government of Tulehu village more ready to develop rural tourism than Liang, (3) Participation and support from local community in develop rural tourism in both village are good, but if they are compared local community in Tulehu are more engage and much high participate than Liang, (4) Perception of tourism from local and national about rural tourism and tourism obyek is still low.